2019
DOI: 10.5005/jp-journals-10071-23292
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dysnatremia and Dyskalemia on Prognosis in Patients with Aneurysmal Subarachnoid Hemorrhage: A Retrospective Study

Abstract: Background: Electrolyte disturbance is one of the complications of subarachnoid hemorrhage (SAH) and its prognostic value is not fully understood. The focus of this study is to evaluate the impact of dysnatremia and dyskalemia on functional outcomes in patients with aneurysmal SAH. Materials and methods: Patients with spontaneous aneurysmal SAH who were admitted to our intensive care unit (ICU) between 1st January 2011 and 31st December 2016 were included. Demographic data, biochemical parameters from days 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Only 20 patients in our study had moderate hypokalemia and no patients with severe hypokalemia. Tam et al found that neither hypokalemia nor hyperkalemia were independent predictors for poor outcome at 3 months after SAH onset ( 22 ). By contrast, others found that only 2% of the patients included were hypokalemic on ED admission, and hypokalemia in the subacute phase (days 7–10) correlated with poor outcome at 3 months after discharge ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only 20 patients in our study had moderate hypokalemia and no patients with severe hypokalemia. Tam et al found that neither hypokalemia nor hyperkalemia were independent predictors for poor outcome at 3 months after SAH onset ( 22 ). By contrast, others found that only 2% of the patients included were hypokalemic on ED admission, and hypokalemia in the subacute phase (days 7–10) correlated with poor outcome at 3 months after discharge ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…33 Both sodium disorders are associated with worse neurological outcomes, especially hypernatremia. [35][36][37][38][39] Furthermore, a recent cohort study showed that greater variability of sodium concentration is also associated with poor neurological outcome. 40 However, sodium disorders are apparently not associated with an increased risk of vasospasm after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, concentrations > 155 mmol/L were associated with unfavorable outcomes within 3 months. 10 More broadly, a study showed that sodium in the blood, in addition to rebleeding, is an independent risk factor, leading to poor prognosis. 14 The role of hyponatremia as a predictor is controversial.…”
Section: Sodium Changementioning
confidence: 99%
“…In most articles, it is demonstrated that it has no prognostic value in the short or long term, especially in terms of mortality. 10,11,15,16 Kieninger et al 17 even demonstrated that the rate of poor outcome at discharge from the intensive care unit (ICU), 6 months after the bleeding event, was significantly lower in patients with moderate hyponatremia (125-129 mmol/L), allowing only a limited conclusion, as the diagnosis of hyponatremia regularly led to early and elaborate measures to achieve rapid normalization of the sodium level and maintain normonatremia in the later course of ICU treatment. A pathophysiological hypothesis proposed by Tam et al 10 would be the ability of brain neurons to adapt to the situation of hyponatremia, in a self-regulation mechanism, managing to reach a state of functional stability in less than 24 hours.…”
Section: Sodium Changementioning
confidence: 99%
See 1 more Smart Citation